2017
DOI: 10.3390/ijerph14070702
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Trace Metal Levels in the General Population of Korea

Abstract: The purpose of this study was to determine the levels of trace metals in the blood of the general Korean population. A total of 258 healthy individuals, according to their regular medical check-ups, (119 males and 139 females, age ranging from 12 to 78 years old) were enrolled from December 2014 to December 2016. Levels of 10 trace elements were determined using inductively coupled plasma mass spectrometry (ICP-MS). The geometric mean (GM) levels for lead, arsenic, cesium, mercury, aluminum, cadmium, copper, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
23
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 62 publications
8
23
1
1
Order By: Relevance
“…In our study, manganese (Mn) in serum of Dolgans was found to be 133 μg/L, which is higher than the literature data (0,58-67,0 μg/L). In our observation, serum Mn in women (135 μg/L) is 16% higher than in men (116 μg/L), which is consistent with a study in Korea, China, Italy, where the female population in the blood Mn by 11-20% higher than men [35][36][37].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In our study, manganese (Mn) in serum of Dolgans was found to be 133 μg/L, which is higher than the literature data (0,58-67,0 μg/L). In our observation, serum Mn in women (135 μg/L) is 16% higher than in men (116 μg/L), which is consistent with a study in Korea, China, Italy, where the female population in the blood Mn by 11-20% higher than men [35][36][37].…”
Section: Discussionsupporting
confidence: 93%
“…The German Human Biomonitoring Commission gives Pb (RV95) in whole blood for men -90 μg/ L, in women -70 μg/L, in children -35 μg/L [56]. The study revealed a GM of 15.97 μg/L for blood Pb in this Korean population, which is lower than that of Chinese (34.9 μg/L), Italian (33.4 μg/L), Spanish (46.7 μg/L), and Brazilian (65.4 μg/L) populations, while the concentration of lead in whole blood was significantly higher in men (21.54 μg/L) than in women (15.07 μg/L) (p < 0.01) [35]. A cohort of 593 middle-aged men exposed to prolonged exposure to low doses of lead was observed.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations